Assessment of Genetic Diversity among Quantitative Traits of Chickpea Genotypes - Dilip Panwar; Anshuman Singh; Harish J; Lakshmeesha R; Sanjay H B; N. Vamsidharreddy (Archives of Current Research International, 2024)
Chickpea (Cicer arietinum L.) is the most important pulse crop providing the livelihood to farmers. India is one of the topmost countries in chickpea production followed by middle-east. Assessment of morphological traits and their genetic diversity will help in increasing production of chickpea. A comprehensive evaluation of 44 distinct chickpea genotypes was conducted during 2020-21 Rabi season at RLBCAU, Jhansi. Utilizing Tocher’s method and D2 values, the studied genotypes were meticulously organized into nine non-overlapping clusters, with cluster (I) comprising the most, featuring 17 genotypes, followed by cluster (II) with 12 genotypes. Significant genetic diversity was evident, especially between clusters (IV) and (VI) (2710.13) followed by (V) and (VI) (2565.51), highlighting the diversity among these genotypes. Key contributors to this divergence were 100-seed weight (48.8%), number of secondary branches per plant (26.5%), and seed yield per plant (9%). Cluster (VIII) exhibited higher mean values for days to maturity (140.57), while cluster (VII) had elevated values for the number of pods per plant (84.61). Genotypes like Phule G 171105, RVSSG 81, RLBG 6, GL-16063, and RKG 19-2 emerged as potential contributors to future breeding programs, promising significant hybrid vigour and superior heterotic segregants to advance chickpea genetics.